ASSISTANCE AND TRAINING IN THE MAKING OF BIOFERTILIZER “UNAIR” WITH LECTURE AND PRACTICE METHODS FOR FARMERS IN KEDUNGPRING VILLAGE, LAMONGAN, TO SUPPORT SUSTAINABLE AGRICULTURE: PENDAMPINGAN DAN PELATIHAN PEMBUATAN PUPUK HAYATI PADA PETANI DI DESA KEDUNGPRING, LAMONGAN, UNTUK MENUNJANG PERTANIAN BERKELANJUTAN - Ni'matuzahroh; Supriyanto, Agus; Affandi, Moch.; Fahmiyah, Indah (Universitas Airlangga, 2024)
Many farmers use chemical fertilizers to increase their agricultural productivity, including farmers in Kedungpring Village, Kedungpring Subdistrict, Lamongan Regency. However, it is currently difficult for farmers to meet their fertilizer needs due to the policy of limiting fertilizer subsidies, therefore farmers must have the independence to meet their fertilizer needs. Biofertilizers can be an alternative because they are easy to make by themselves, and are more environmentally friendly than chemical fertilizers. Assistance and training on biofertilizer production for farmers in Kedungpring Village, Lamongan is needed. The purpose of this community service activity is to increase the knowledge of farmers in Kedungpring Village, Lamongan about biological fertilizers, and have the ability to make biological fertilizers, so that they can meet their fertilizer needs. This activity begins with the coordination and planning stages of the activity, providing material on biofertilizers to increase farmers' knowledge of biofertilizers using the lecture method, assistance and training in making biofertilizers using the lecture and practice methods so that farmers have the ability to make biofertilizers, and monitoring and evaluation carried out by the follow-up method. Based on the community service activities carried out, farmers' knowledge about biofertilizers has increased, which is indicated by most farmers having a higher post-test score than the pre-test score, also farmers are able to make their own biofertilizers which are indicated by the color of cloudy brown fertilizer and the distinctive sour smell of fermentation. Through this Community Service activity, farmers in Kedungpring Village also received six bioreactors for making biological fertilizers. Through this whole series of activities, it is an effort to realize sustainable agriculture, and it is hoped that farmers in Kedungpring Village, Lamongan can meet their fertilizer needs independently.